Frost Survival Mechanism of Vegetative Buds in Temperate Trees: Deep Supercooling and Extraorgan Freezing vs. Ice Tolerance - Neuner, Gilbert; Monitzer, Kristina; Kaplenig, Dominik; Ingruber, Julia (Frontiers in Plant Science, 2019)
In temperate climates, overwintering buds of trees are often less cold hardy than adjoining stem tissues or evergreen leaves. Yet, scarce data are available about freezing resistance (FR) of buds and the underlying functional frost survival strategy that in case of supercooling can restrict the geographic distribution. Twigs of 37 temperate woody species were sampled in midwinter 2016 in the Austrian Inn valley. After assessment of FR, infrared-video-thermography and cryo-microscopy was used to study the freezing pattern in and around overwintering vegetative buds. Only in 4 species, after controlled ice nucleation in the stem (-1,6±0,9°C) ice was observed to immediately invade the bud. These buds tolerated extracellular ice and were the most freezing resistant (-61,8°C mean LT50). In all other species (33), the buds remained supercooled and free of ice, despite a frozen stem. A structural ice barrier prevents ice penetration. Extraorgan ice masses grew in the stem and scales but in 50 % of the species only between premature supercooled leaves. Two types of supercooled buds were observed: in temporary supercooling buds (14 species) ice spontaneously nucleated at -20,5±4,6°C. This freezing process appeared to be intracellular as it matched the bud killing temperature (-22,8°C mean LT50). This response rendered temporarily supercooled buds as least cold hardy. In 19 species, the buds remained persistently supercooled down to below the killing temperature without indication for the cause of damage. Although having a moderate midwinter FR of -31,6°C (LT50), some species within this group attained a FR similar to ice tolerant buds. This variability could indicate mechanistic differences. The present study represents the first comprehensive overview of frost survival mechanisms of vegetative buds of temperate trees. Except for four species that were ice tolerant, the majority of buds survive in a supercooled state, remaining free of ice. In 50 % of species, extraorgan ice masses innoxiously grew between premature supercooled leaves. Despite exposure to the same environmental demand, midwinter FR of buds varied intra-specifically between -17,0 and -90,0°C. Particularly, species, whose buds are killed after temporary supercooling, have a lower maximum FR, which limits their geographic distribution.